2003
DOI: 10.1074/jbc.m309591200
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-selective Functional Domains of Perilipin A Differentially Regulate Constitutive and Protein Kinase A-stimulated Lipolysis

Abstract: Perilipin (Peri) A is a lipid droplet-associated phosphoprotein that acts dually as a suppressor of basal (constitutive) lipolysis and as an enhancer of cyclic AMPdependent protein kinase (PKA)-stimulated lipolysis by both hormone-sensitive lipase (HSL) and non-HSL(s). To identify domains of Peri A that mediate these multiple actions, we introduced adenoviruses expressing truncated or mutated Peri A and HSL into NIH 3T3 fibroblasts lacking endogenous perilipins and HSL but overexpressing acyl-CoA synthetase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 42 publications
(47 reference statements)
9
136
0
2
Order By: Relevance
“…These observations suggest that the unique carboxyl terminus of perilipin A serves a shielding function against cytosolic lipases. A very recent report (27) has reported similar findings that the final 216 amino acid peptide of the carboxyl terminus of perilipin A serves an important role in reducing levels of basal lipolysis by non-HSL lipases; however, that study suggests that the amino terminus of perilipin A lacks protective function. We note that study of the larger amino-terminal truncations described in the recent report may have missed the effects that we have uncovered.…”
Section: Discussionmentioning
confidence: 68%
“…These observations suggest that the unique carboxyl terminus of perilipin A serves a shielding function against cytosolic lipases. A very recent report (27) has reported similar findings that the final 216 amino acid peptide of the carboxyl terminus of perilipin A serves an important role in reducing levels of basal lipolysis by non-HSL lipases; however, that study suggests that the amino terminus of perilipin A lacks protective function. We note that study of the larger amino-terminal truncations described in the recent report may have missed the effects that we have uncovered.…”
Section: Discussionmentioning
confidence: 68%
“…They bring about lipid accumulation and the adipocyte phenotype. It has previously been shown that cAMP and PKA are implicated in the regulation of lipid accumulation or lipolysis [26][27][28][29][30][31]. To avoid interference from the lipolysis effect of cAMP and PKA, all specific reagents used in this study (such as forskolin, SQ22536, 8-Br-cAMP and H89) were only presented in cell culture in the first 2 days of the entire induction period of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ/Ϫ MEF Adipocytes-Adenoviruses expressing Aequoria victoria green fluorescent protein (Ad-GFP) or wild-type perilipin A (Ad-WT Peri A) were generated and verified as described previously (13,14,32). Recombinant adenovirus was transduced into Peri Ϫ/Ϫ MEFs with Lipofectamine Plus TM (Invitrogen) on day 3 after induction of differentiation.…”
Section: Adenoviral Expression Of Gfp and Peri A Constructs In Perimentioning
confidence: 99%